The Representation of the universitas fidelium in the councils of the conciliar period - Gill, Joseph (Studies in church history, 1971)
The Council of Pisa was the fruit of a long period of gestation. Intermittently over centuries canonists had discussed where in various contingencies the supreme authority in the Church lay—with the pope, the cardinals, the universitas fidelium in a general council. Twice in the fourteenth century theory was nearly tested by practice, when Philip the Fair opposed Boniface VIII and when Louis of Bavaria faced John XXII. The final challenge was given by the Great Schism. Begun in 1378 it dragged on for decades, causing irreparable damage to Christian Europe. Neither of the rival ‘popes’ showed any genuine goodwill to end it. So others, particularly in France, lent a hand. When Benedict XIII in Avignon refused the via cessionis (abdication) and paid only lip-service to the via discussionis, the court of Paris withdrew its obedience and the theologians of the French universities justified the royal action.